A pilot study of a mindfulness-based program (mbsoccerp): the potential role of mindfulness, self-compassion and psychological flexibility on flow and elite performance in soccer athletes - Carraça, B.; Serpa, S.; Rosado, A.; Palmi Guerrero, J. (Revista Iberoamericana de Psicologia del Ejercicio y el Deporte, 2019)
Mindfulness-based interventions have consistently demonstrated associations with multiple aspects of flow and sport performance. In this current pilot study we sought to explore the effects of Mindfulness-based program for elite soccer athletes (MBSoccerP) training on self-compassion, mindfulness, and psychological flexibility, flow and sport performance outcomes on a sample of 57 elite soccer players (Portuguese 2ª league) from two different cohorts participated in this study. Also, we examined the relationship between mindfulness, psychological flexibility, and self-compassion at baseline-predicted flow and performance measures. Paired t-tests and correlations were conducted to examine changes and significant relation between variables before and after the MBSoccerP intervention. Also hierarchical regression was used to assess the influence of baseline psychological flexibility, self-compassion, and mindfulness facets on flow and sport performance measures at post-intervention in this pre-/post-pilot study. Results suggested that mindfulness, self-compassion, direct forms of performance and flow improved from pre to post-intervention and psychological inflexibility decreased. Further, mindfulness predicted higher flow at post intervention while controlling for baseline mindfulness. Psychological inflexibility predicted lower dispositional flow at post intervention. Findings suggest that MBSoccerP may be effective for improving flow and performance